2018
DOI: 10.1038/s41586-018-0623-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic landscape of acute myeloid leukaemia

Abstract: The implementation of targeted therapies for acute myeloid leukemia has been challenged by complex mutational patterns within and across patients as well as a dearth of pharmacologic agents for most mutational events. Here, we report initial findings from the Beat AML program on a cohort of 672 tumor specimens collected from 562 patients. We assessed these specimens using whole exome sequencing, RNA-sequencing, and ex vivo drug sensitivity analyses. Our data reveal Users may view, print, copy, and download tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

34
1,150
5
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,051 publications
(1,242 citation statements)
references
References 82 publications
34
1,150
5
7
Order By: Relevance
“…To the best of our knowledge, the impact of VAF for ASXL1, DNMT3A, JAK2, TET2, and TP53 mutations has not been evaluated extensively previously. 19 Therapeutic agents targeting ASXL1, DNMT3A, JAK2, TET2, and TP53 mutations might be necessary for improved outcome. The TP53 VAF was the major driver for worse survival as demonstrated on multivariate analysis, which demonstrated that each increasing increment in the VAF percentage was associated with a 1% higher risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the impact of VAF for ASXL1, DNMT3A, JAK2, TET2, and TP53 mutations has not been evaluated extensively previously. 19 Therapeutic agents targeting ASXL1, DNMT3A, JAK2, TET2, and TP53 mutations might be necessary for improved outcome. The TP53 VAF was the major driver for worse survival as demonstrated on multivariate analysis, which demonstrated that each increasing increment in the VAF percentage was associated with a 1% higher risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…21 The BEAT AML program reported on ex vivo drug sensitivity analyses and demonstrated that currently available targeted therapy could not target ASXL1, DNMT3A, JAK2, TET2, and TP53 mutations, except for several potential agents that target DNMT3A mutations. 19 Therapeutic agents targeting ASXL1, DNMT3A, JAK2, TET2, and TP53 mutations might be necessary for improved outcome.…”
Section: Discussionmentioning
confidence: 99%
“…33 A most recent gene profiling work performed with uncultured and untreated samples presented a large functional genomic data set of primary AML bone marrow mononuclear cells and revealed new markers and mechanisms of drug sensitivity and resistance. 6 Additionally, the ex vivo drug testing of 122 small molecule inhibitors was done in 2D culture for a short duration of 4 days and did not include Ara-C. There is about 20% overlap in mutated genes identified from this study compared to ours, indicating genetic markers predicting common drug responsiveness.…”
Section: Discussionmentioning
confidence: 80%
“…APP ranks 19 in our top 100 gene list for predicting Ara‐C responsiveness and was reported to be one of the potential candidate pathway genes of relevance for pharmacogenetic studies on ara‐C and other nucleoside analogs . A most recent gene profiling work performed with uncultured and untreated samples presented a large functional genomic data set of primary AML bone marrow mononuclear cells and revealed new markers and mechanisms of drug sensitivity and resistance . Additionally, the ex vivo drug testing of 122 small molecule inhibitors was done in 2D culture for a short duration of 4 days and did not include Ara‐C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation